China’s transition to low carbon society: drivers and implementation strategies - Li, Jun (Elgar Online, 2015)
Faced with increasingly socioeconomic and environmental challenges at the turn of the century, the Chinese government has unveiled a blueprint for building an environmentally friendly,low carbon and harmonious society by 2020 in its latest socioeconomic development plan. This chapter will investigate both the strengths and weaknesses of climate policy in China based on a comprehensive review of national and sectoral policies which expect to facilitate China’s transition to a low carbon society in the next couple of decades. The low carbon policy implementation strategies will be discussed in detail for three large carbon-emitting sectors in China, namely industry, power and buildings.